Changes in sprint start performance due to variation in block pedal angles on non-experienced, but coached participants - Salo, A. I. T.; Colyer, S. L.; Sheppard, J. J.; Okkonen, O. (ISBS Proceedings Archive (Michigan), 2018)
Athletes have considerable freedom to set the starting blocks in athletics sprint events. We aimed to understand how the block pedal angle changes influence force production and performance of the start. Fifteen non-experienced, but coached participants performed a total of 18 starts each (three starts with each of six different block settings) in a random order. Linear mixed modelling of ground reaction forces (1000 Hz) and motion data (200 Hz) yielded 6.4% higher values (p<0.05) of average horizontal external power with block pedal angles of 40° in comparison to 60° angles. Varying the pedal angles induced joint angle changes at the set position, which in turn resulted in increased force production at the lower pedal angles. This was probably due to more favourable muscle-tendon unit lengths for force production at the lower block pedal angles.